Sosialisasi Mewujudakan Keadilan Sosial dengan Membangun Kesadaran Stop Bullying di Kalangan Pelajar - Yulsi M. Nitte; Ike Septa F. Muktyawati; Intan Nur Amaliah Ramadhani; Demsi Adonia Poel; Denti Sariani Mauboi; Lediana Susanti (Kolaborasi : Jurnal Hasil Kegiatan Kolaborasi Pengabdian Masyarakat, 2024)
In accordance with the title, we created this journal with the aim of preventing bullying, especially among teenagers, because currently there are many cases of bullying among teenagers ranging from elementary school, junior high school, to high school. Not infrequently the consequences of this bullying are life-threatening. Preventing bullying is one example of bullying behavior. By using counseling methods in the adolescent play environment where bullying often occurs, if not handled quickly, bullying cases will claim more victims, the perpetrators cannot be controlled and the victims live uneasy.